2017
DOI: 10.1002/dvg.23085
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of mice carrying a conditional TEAD1 allele

Abstract: The Hippo-YAP pathway is essential for controlling organ size and tumorigenesis. Previous studies have demonstrated that the primary outcome of YAP signaling in the nucleus is achieved by interaction with the transcription factor TEAD1. The YAP/TEAD1 complex binds to DNA element and regulates the expression of genes involved in cell growth. However, constitutive knockout of TEAD1 leads to early embryonic lethality in mice. Thus, generation of a floxed TEAD1 mouse becomes crucial for further understanding mid- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…We additionally knocked-down the TEAD isoforms in cells expressing TAZ 4SA , i.e., with high TAZ repressor activity. As shown in Figure A4 of the Appendix A , NSPCs express mainly TEAD1 and TEAD2 which have been reported to cooperate in notochord maintenance as well as cell proliferation and survival in mouse development [ 45 , 46 ]. Knock-down of TEADs ( Figure 7 F) resulted in low levels of CTGF and CYR61 transcripts as expected ( Figure 7 G), but, importantly, we observed the increase in SOX2 and the ASCL1 , NEUROG2, and NEUROD1 proneuronal transcripts ( Figure 7 H), indicating that TAZ requires TEAD co-partners to exert repressor activity on neuronal differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…We additionally knocked-down the TEAD isoforms in cells expressing TAZ 4SA , i.e., with high TAZ repressor activity. As shown in Figure A4 of the Appendix A , NSPCs express mainly TEAD1 and TEAD2 which have been reported to cooperate in notochord maintenance as well as cell proliferation and survival in mouse development [ 45 , 46 ]. Knock-down of TEADs ( Figure 7 F) resulted in low levels of CTGF and CYR61 transcripts as expected ( Figure 7 G), but, importantly, we observed the increase in SOX2 and the ASCL1 , NEUROG2, and NEUROD1 proneuronal transcripts ( Figure 7 H), indicating that TAZ requires TEAD co-partners to exert repressor activity on neuronal differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…To determine the functional role of TEAD1 in vivo, we first performed wire injury in LFA in Tead1 global HET (heterozygous) mice because Tead1 global KO mouse is embryonic lethal. 22,24 Characterization of the Tead1 HET mice demonstrated that TEAD1 protein expression in HET mice is reduced to ≈50% in both aortic and heart tissues compared with WT (wild type) control mice. This decreased TEAD1 expression did not affect SM or cardiac contractile protein expression or gross morphology of intact right femoral artery (Online Figure IIA through IID).…”
Section: Resultsmentioning
confidence: 99%
“…Tead1 global heterozygote mice were generated as we recently reported. 24 SM-specific Tead1 iKO (inducible KO) mice were generated by crossing female Tead1 F mice 24 with male mice expressing tamoxifen-inducible Cre driven by the SM-specific gene Myh11 (SM myosin heavy chain [SM MHC]) Myh11-CreER T2+ ) Only male mice were used in this study because SM MHC-CreER T2 transgene is only localized in the Y chromosome. 25 At 10 weeks of age, male mice ( Myh11-CreER T2+ /Tead1 F/F ) were randomly assigned to 2 groups.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most well-known roles of TEADs is in heart morphogenesis, where TEAD1 is required for cardiomyocyte proliferation (Liu et al, 2019;Wen et al, 2019). Ubiquitous deletion of mouse Tead1 causes embryonic lethality with heart defects (Chen et al, 1994;Wen et al, 2017), and cardiomyocytespecific deletion of Tead1 results in perinatal lethality (Liu et al, 2019). Conversely, striated muscle-specific overexpression of Tead1 causes cardiac dysfunction (Tsika et al, 2010).…”
Section: Teads Function In Response To a Variety Of Cuesmentioning
confidence: 99%